2015
DOI: 10.1001/jama.2015.17296
|View full text |Cite
|
Sign up to set email alerts
|

Live-Birth Rate Associated With Repeat In Vitro Fertilization Treatment Cycles

Abstract: Among women in the United Kingdom undergoing IVF, the cumulative prognosis-adjusted live-birth rate after 6 cycles was 65.3%, with variations by age and treatment type. These findings support the efficacy of extending the number of IVF cycles beyond 3 or 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(151 citation statements)
references
References 30 publications
(50 reference statements)
8
139
1
1
Order By: Relevance
“…Previous studies (23,24) also support our finding that the cumulative live birth rate increased after three or four IVF cycles, reinforcing the efficacy of extending treatment beyond three or four IVF cycles. We believe that this is also applies to women with symptomatic endometriosis who have failed several IVF treatments.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies (23,24) also support our finding that the cumulative live birth rate increased after three or four IVF cycles, reinforcing the efficacy of extending treatment beyond three or four IVF cycles. We believe that this is also applies to women with symptomatic endometriosis who have failed several IVF treatments.…”
Section: Discussionsupporting
confidence: 87%
“…If one has 2 embryos, and the choice is to transfer 2 in 1 cycle, or 1 each in 2 cycles, data have shown that the overall pregnancy rate is actually higher with 2 in 1 cycle [126][127][128] . There is the potential for DCDA twins and rarely dichorionic-triamniotic triplets.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, cumulative livebirth rates are often reported either as one overall average rate or stratified by the woman's age or type of infertility at a national or IVF clinic level. [7][8][9][10][11] Given that many other patient and treatment characteristics can affect the success of IVF or ICSI, 12 it can be difficult for clinicians to counsel couples as to their individualised chances of success over a complete package of IVF or ICSI treatment.…”
Section: Introductionmentioning
confidence: 99%